Effect of microstructure on fracture behavior of freestanding plasma sprayed 7 wt.% Y2O3 stabilized ZrO2. Issue 7 (July 2021) - Lal, Devi; Kumar, Praveen; Bathe, Ravi; Sampath, Sanjay; Jayaram, Vikram
Abstract: Air plasma sprayed (APS) 7 wt.% yttria-stabilized zirconia (7YSZ) coatings have a multitude of microstructural defects, at various length scales, such as pores, intra-splat and inter-splat micro-cracks, which cumulatively affect the mechanical properties and fracture behavior of the material. This microstructure is also susceptible to changes including sintering during high temperature operation. The kinetics of "healing" of these microstructural defects are widely different, such that the smallest defects heal at significantly lower temperatures and in shorter periods. Here, the effect of thermal exposure-induced change in the microstructure on the fracture behavior, in terms of crack path and apparent fracture energy, of free-standing APS 7YSZ has been examined using miniaturized cantilever samples. Femto-second laser ablation technique was used to fabricate a sharp notch in the sample. Apparent fracture toughness in Mode I increased with the bending modulus of the material, revealing a monotonic effect of the density, which directly affects the modulus of the coating, on the overall fracture resistance of the coating. The relative density, crack tortuosity and the average apparent fracture energy of the as-deposited coating were 0.82, 2.1 and 62 ± 15 J/m 2, respectively, which evolved to 0.94, 1.2 and 170 ± 30 J/m 2, respectively, after a heat treatment at 1300 °C for 100 h. The detailed microstructural characterization and fractography revealed that the healing of inter-splat and intra-splat cracks led to the transition from fracture along the splat interface to quasi-cleavage fracture through the splats, thereby increasing the fracture resistance of these coatings toward monolithic fully-dense 7YSZ. The work readily reveals the relative importance of defects at various length scales on the overall energy absorbed during fracture of the coating.